2017
DOI: 10.1161/circheartfailure.116.003709
|View full text |Cite
|
Sign up to set email alerts
|

Increased Thromboembolic Events With Dabigatran Compared With Vitamin K Antagonism in Left Ventricular Assist Device Patients

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 29 publications
2
51
0
2
Order By: Relevance
“…There are insufficient dosing and safety data for their use in children. Of note, DOACs have failed in trials of artificial valves [256] and circuits [257], so their effectiveness in the setting of graft material (such as that used in extracardiac Fontan surgery) remains to be proven.…”
Section: Thromboprophylaxismentioning
confidence: 99%
“…There are insufficient dosing and safety data for their use in children. Of note, DOACs have failed in trials of artificial valves [256] and circuits [257], so their effectiveness in the setting of graft material (such as that used in extracardiac Fontan surgery) remains to be proven.…”
Section: Thromboprophylaxismentioning
confidence: 99%
“…Antithrombotics are the cornerstone therapy in the outpatient management of LVAD. In addition to aspirin, warfarin is the anticoagulant of choice, while direct thrombin inhibitors (e.g., dabigatran) have failed to ascertain their usefulness in these patients [36]. Dabigatran was studied in a prospective randomized study in which 30 patients were randomized to either dabigatran or phenprocoumon (vitamin K antagonist).…”
Section: Managementmentioning
confidence: 99%
“…Dabigatran was studied in a prospective randomized study in which 30 patients were randomized to either dabigatran or phenprocoumon (vitamin K antagonist). This trial was prematurely discontinued due to the increased thromboembolic phenomenon observed in half of the patients (four out of eight) receiving dabigatran [36]. On warfarin therapy, the target INR is 2.0 -3.0 in LVAD patients [30].…”
Section: Managementmentioning
confidence: 99%
“…A small study of 7 patients using dabigatran showed no excess rate of bleeding or thrombosis . However, a single‐center, randomized trial of dabigatran vs. warfarin was terminated early due to increased thromboembolic events associated with dabigatran . Furthermore, given the negative experience with dabigatran use in mechanical heart valves, routine use cannot be recommended until ongoing clinical trials are completed.…”
Section: Management Strategiesmentioning
confidence: 99%